O reconhecimento dos direitos LGBT como direitos humanos. - Gorisch, Patrícia Cristina Vasques de Souza (2013)
This term aims to demonstrate the evolution of the LGBT (lesbian, gay, bisexual and transgender) struggle since the Stone Wall Uprising, when the LGBT people finally imposed their civil rights, making the first gay parade ¿ just to get the attention of the whole society that the LGBT people exist and should be treated as citizens. The evolution of human thought of LGBT rights knocked on the doors of the UN many years ago, but finally in 2011 ¿ the same year that here in Brazil, the Supreme Court considered same-sex couple as a family entity and the Court of Justice allowed the marriage of a pair of lesbians ¿ the United Nations issued a landmark resolution condemning discrimination on sexual orientation and gender identity. We will defend the right to sexuality as inherent human attribute and therefore linked to the right to life, making an analysis of systems of human rights protection such as global and regional as well as national, linking Brazil to this resolution because it as was one of proponents and voters. This historical Resolution, places once and for all the LGBT rights on the map of human rights.